Totally-green Fuels via CO2 Hydrogenation - Lorenzo Spadaro; Alessandra Palella; Francesco Arena (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Hydrogen is the cleanest energy vector among any fuels, nevertheless, many aspects related to its distribution and storage still raise serious questions concerning costs, infrastructure and safety. On this account, the chemical storage of renewable-hydrogen by conversion into green-fuels, such as: methanol, via CO2 hydrogenation assumes a role of primary importance, also in the light of a cost-to-benefit analysis. Therefore, this paper investigates the effects of chemical composition on the structural properties, surface reactivity and catalytic pathway of ternary CuO-ZnO-CeO2 systems, shedding light on the structure-activity relationships. Thus, a series of CuZnCeO2 catalysts, at different CuO/CeO2 ratio (i.e. 0.2-1.2) were performed in the CO2 hydrogenation reactions at 20 bar and 200-300 °C, (GHSV of 4800 STP L∙kg∙cat-1∙h-1). Catalysts were characterized by several techniques including X-ray Diffraction (XRD), N2-physisorption, single-pulse N2O titrations, X-ray Photoelectron Spectroscopy (XPS), and Temperature-programmed Reduction with H2 (H2-TPR). Depending on preparation method, the results clearly diagnostics the occurrence of synergistic structural-electronic effects of cerium oxide on copper activity, with an optimal 0.5 copper-to-cerium content. The rise of CuO loading up to 30% drives to a considerable increase of hydrogenation activity: C2Z1-C catalyst obtains the best catalytic performance, reaching methanol yield value of 12% at 300 °C. Catalyst activity proceeds according to volcano-shaped relationships, in agreement with a dual sites mechanism. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).